MIGRACIYA TARIYXÍ – BUL INSANIYAT TARIYXÍ - Utepova, Genjexan Baltabaevna (ILIM hám JÁMIYET, 2026)
This article mainly discusses the migration movements (migration) of the world’s population in historical periods, economic, demographic, political, social, and ecological factors influencing migration movements.